SISTEM INFORMASI PELAYANAN ADMINISTRASI BERBASIS WEBSITE DENGAN METODE RUP (RATIONAL UNIFIED PROCESS) (STUDI KASUS KANTOR URUSAN AGAMA KECAMATAN PANJALU) - M Ikmal Wiawan; Rama Fadillah; Dede Maulana Yusup (STKIP PGRI Situbondo, 2023)
The services provided by the government to the people continue to experience updates both in terms of paradigm and service format along with increasing public demands and changes within the government itself. At this time, the process of submitting letters provided by the religious affairs office of Panjalu sub-district to the community is still carried out manually, namely by visiting the office directly. This is due to the splitting or revitalization of the religious affairs office of Panjalu sub-district. Thus the information process obtained is ineffective and requires a long time in processing all administrative matters. Related to this, an administrative service information system is needed that can provide convenience in processing information effectively and can speed up the administrative process. In this study, a website-based administrative service information system was developed with the Rational Unified. This method is known as the Integrated Process Model because it has two axes that show dynamic and static aspects, and also has an iterative approach. The results of this research are in the form of an administrative service information system that can make it easier for the public to get information and speed up the process of submitting letters.